2013
DOI: 10.1177/0883073813493502
|View full text |Cite
|
Sign up to set email alerts
|

Hemisphere Differences in Speech-Sound Event-Related Potentials in Intensive Care Neonates

Abstract: Neurodevelopmental delays in intensive care neonates are common but difficult to predict. In children, hemisphere differences in cortical processing of speech are predictive of cognitive performance. We hypothesized that hemisphere differences in auditory event-related potentials in intensive care neonates are predictive of neurodevelopment in infancy, even in those born preterm. Event-related potentials to speech sounds were prospectively recorded in 57 infants (gestational age 24–40 weeks) prior to discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Amongst all aspects of poor outcome in preterm infants, language development is commonly impaired (2). Previous studies indicated that infants with poor language performance at school age show abnormalities in electrocortical signals already in the neonatal period (3,6). Mehta et al showed that abnormalities in conventional EEG are present in 64.5% of infants with speech and language impairment (5).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst all aspects of poor outcome in preterm infants, language development is commonly impaired (2). Previous studies indicated that infants with poor language performance at school age show abnormalities in electrocortical signals already in the neonatal period (3,6). Mehta et al showed that abnormalities in conventional EEG are present in 64.5% of infants with speech and language impairment (5).…”
Section: Discussionmentioning
confidence: 99%
“…Auditory enrichment facilitates the development of the auditory cortex and stimulates the progression of neural arborisation and synaptogenesis [2,3]. Evidence from several studies demonstrates that the preterm infant's ability to process cortical signals is a significant factor affecting the development of receptive and expressive language skills [4,5,50].…”
Section: Discussionmentioning
confidence: 99%
“…By 35 weeks, differentiation of phonemes is possible and the fetus can now dis-DOI: 10.1159/000489600 criminate voice and sustain auditory memory [2]. However, for infants born preterm (especially < 28 weeks) this development occurs in the abnormal environment of the neonatal unit, during a critical period of neural arborisation and synaptogenesis [3]. Significant delays have been found in auditory brainstem responses of preterm infants at a term-equivalent age, reflecting atypical brainstem maturation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because speech-sound discrimination is associated with cognitive and communication outcomes in early childhood, 19,20 future studies should examine whether continued administration of caffeine age in the most immature infants would improve cortical processing as it does in the more mature infants.…”
Section: Discussionmentioning
confidence: 99%